Regulation of the tolerogenic function of steady‐state DCs. Issue 4 (20th March 2014) - Probst, Hans Christian; Muth, Sabine; Schild, Hansjörg
<x xml:space="preserve">Abstract</x> Dendritic cells (DCs) are master regulators of T‐cell responses. After sensing pathogen‐derived molecular patterns (PAMPs), or signals of inflammation and cellular stress, DCs differentiate into potent activators of naïve CD4+ and CD8+ T cells through a process that is termed DC maturation. By contrast, DCs induce and maintain peripheral T‐cell tolerance in the steady state, that is in the absence of overt infection or inflammation. However, the immunological steady state is not devoid of DC‐activating stimuli, such as commensal microorganisms, subclinical infections, or basal levels of proinflammatory mediators. In the presence of these activating stimuli, DC maturation must be calibrated to ensure self‐tolerance yet allow for adequate T‐cell responses to infections. Here, we review the factors that are known to control DC maturation in the steady state and discuss their effect on the tolerogenic function of steady‐state DCs.